2006
DOI: 10.1074/jbc.m606613200
|View full text |Cite
|
Sign up to set email alerts
|

N-(3-Oxo-acyl)homoserine Lactones Signal Cell Activation through a Mechanism distinct from the Canonical Pathogen-associated Molecular Pattern Recognition Receptor Pathways

Abstract: Innate immune system receptors function as sensors of infection and trigger the immune responses through ligand-specific signaling pathways. These ligands are pathogen-associated products, such as components of bacterial walls and viral nuclear acids. A common response to such ligands is the activation of mitogen-activated protein kinase p38, whereas doublestranded viral RNA additionally induces the phosphorylation of eukaryotic translation initiation factor 2␣ (eIF2␣). Here we have shown that p38 and eIF2␣ ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
164
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(175 citation statements)
references
References 68 publications
11
164
0
Order By: Relevance
“…It has been established that the 3-oxo-C12-HSL produced by P. aeruginosa impairs the ability of mammalian cells to respond to the invading bacterial pathogen via the innate immune system (Kravchenko et al, 2008;Kravchenko et al, 2006;Shiner et al, 2006). One of the key steps in this response immediately after receptor-recognition of the pathogen is the activation of the nuclear transcription factor NF-B and consequential expression of genes encoding pro-inflammatory cytokines.…”
Section: Ahl Effect On Human and Plant Cellsmentioning
confidence: 99%
“…It has been established that the 3-oxo-C12-HSL produced by P. aeruginosa impairs the ability of mammalian cells to respond to the invading bacterial pathogen via the innate immune system (Kravchenko et al, 2008;Kravchenko et al, 2006;Shiner et al, 2006). One of the key steps in this response immediately after receptor-recognition of the pathogen is the activation of the nuclear transcription factor NF-B and consequential expression of genes encoding pro-inflammatory cytokines.…”
Section: Ahl Effect On Human and Plant Cellsmentioning
confidence: 99%
“…When CF patients become colonized with P. aeruginosa, the bacteria secrete quorum-sensing molecules, including N-(3-oxo-dodecanoyl)-S-homoserine lactone (3O-C12) and butyryl homoserine lactone, to signal each other and to regulate their own gene expression, including genes involved in formation of biofilms (1)(2)(3)(4)(5)(6). Concentrations of 3O-C12 in CF sputum are thought to be in the nanomolar range (7) but reach 5 M in P. aeruginosa supernatants and may reach Ͼ100 M in regions adjacent to biofilms (8,9).…”
mentioning
confidence: 99%
“…3O-C12 operates through TLR-and Nod/Ipaf/caterpillarindependent signaling to activate multiple proinflammatory genes that are associated with NF-B signaling, including IL8, Cox2, and MUC5AC in both epithelial and other cell types (7)(8)(9)(10)(11)(12). Some of these proinflammatory effects may be mediated through activation of MAPKs (8,9) or Ca 2ϩ (7,13) or inhibition of peroxisome proliferator-activated receptor ␥ (14). However, 3O-C12 also inhibits NF-B signaling and expression of proinflammatory cytokines in macrophages and primary human bronchial airway epithelial cells (9) when cells are treated with both 3O-C12 and another agonist like LPS or TNF␣ that activates NF-B on its own.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the biochemical effects of AHLs on mammalian cells (Kravchenko et al, 2006;Ritchie et al, 2003;Smith et al, 2002a;Smith et al, 2002b;Telford et al, 1998). Notably, 3-oxo-C 12 -HSL specifically promotes induction of apoptosis in macrophages and neutrophils (Tateda et al, 2003).…”
Section: Introductionmentioning
confidence: 99%